A központi hatalmak Ukrajna-politikája és a Szövetség Ukrajna Felszabadításáért kudarca, 1914-1917 - Kurdi Krisztina (Egyesület Közép-Európa Kutatására Szeged, 2019)
The focus of my paper is the activities of the Union for the Liberation of Ukraine (SVU). The organization was founded in 4. August 1914 in Lemberg (Galicia) by a number of Ukrainian emigré politicians from Russian Empire who had taken refuge in the Austro-Hungarian Empire before the outbreak of the First World War. The SVU initially headed by Dmytro Doncov and consisted also Mykola Zaliniak, Volodymyr Doroshenko, and Oleksander Skoropys-Yoltukhovsky. It was assisted also by few Galician and Bukovinian polititicians. They hoped to establish an independent Ukrainian state with the support of the Central Powers. Initially, the SVU was oriented toward Vienna rather than Berlin. The activity of the Union was financed by Germany and Austria, although none would commit itself publicly or privately to an independent Ukraine. The most successful area of their activity was the information and publications work and the educational and cultural work in prisoners of war camps. As a result of Union efforts two Ukrainian army divisions were formed.
Keywords: Bölcsészettudományok; Történettudomány és régészet